The Role of PKN Teachers in Providing Moral Education to Students in Class X.Ips 1 and X.Ips 2 SMA Negeri 1 Bilah Hulu - Panggabean, Rotua Lusianti; Adi, Panggih Nur (Budapest International Research and Critics University, 2022)
The purpose of the study was to find out the efforts made by civics teachers in providing moral education to students in class X.IPS1 and class X.IPS 2 SMA Negeri 1 Bilah Hulu and to find out the teacher's obstacles in providing moral education to students in class X.IPS1 and Class X.IPS 2 SMA Negeri 1 Blade Hulu. This research was conducted at SMA Negeri 1 Bilah Hulu from November to December 2021 using data triangulation. This type of research is in the form of descriptive with a qualitative approach. From the research results obtained from the literature and the distribution of questionnaires to respondents, namely very good 25 people (42%), good 10 people (17%), and enough 15 people (25%), not good 10 people (16%).